Galangal phytocompounds in tumour tactics - an in silico Analysis targeting breast cancer - ARCHANA DAS; SANTHY, K.S (International Journal of Pharma and Bio Sciences, 2017)
Current research in drug discovery from medicinal plants provides novel and important leads against cancer targets. In the present study, breast cancer proteins docked with natural compounds derived from the plant, Alpinia galanga (L.) Willd offers a great hope in the identification of drug targets and potential lead compounds. Lig Prep module was used to retrieve all molecules from GC-MS results and processed it to be docked with diseased protein. The drug likeliness and toxicity of the selected molecules were performed using QikProp module from Schrodinger. Glide module identifies favorable interactions between lead molecules and receptors and the best complex was analyzed through Desmond. Principal descriptors and property predictions of lead compounds were observed to be under the acceptable limit. Nortrachelogenin was best docked with KLRG1 (-7.24 Kcal/mole) and STK10 (-7.21 Kcal/mole). Alpha-terpineol was best bound to BAX (-5.42 Kcal/mole). 3-phenyl-2-butanone showed multiple binding interactions with PTEN, CHEK1, PALB2 and BRCT7. Simulation interactions revealed that Checkpoint kinase1 complexes with 3-phenyl-2-butanone as the best complex. Altogether the findings explored the unique potential of galangal phytocompounds in future cancer therapies with less undesirable side effects